Determinants of mining sector stock price in the indonesian sharia stock index (issi): panel data analysis of 14 mining sector companies - Nela Cahyaningtyas; Siti Aisyah (Jurnal Ekonomi, 2024)
The mining sector has considerable influence on the national and global economy as well as financial markets, where changes in share prices in the mining sector can influence investment portfolios and government regulatory policies. The main objective of this research is to see the influence of exchange rates, interest rate, world coal prices, mining exports, and stock trading volume on mining sector stock prices in the Indonesian Sharia Stock Index (ISSI) in the period of January 2020 to January 2023. It was carried out using panel data analysis. Fixed Effect Model (FEM) is the selected model. The sample was drawn using a purposive sampling method, where 14 mining sector companies in the ISSI were obtained that met the criteria as companies operating in the coal sub-sector and the number of shares traded each month was not 0. Research findings indicate that the share price was influenced by two factors, world coal prices which have a positive and significant influence, and share trading volume which has a negative and significant influence on mining sector share prices. Meanwhile, the exchange rate, interest rates, and mining exports do not affect mining sector share prices. This research is useful in preparing analytical models and analytical frameworks to estimate changes in stock price in the mining sector, thus helping investors, analysts, and companies in making investment decisions.